mom identifies a receptor for the Drosophila JAK/STAT signal transduction pathway and encodes a protein distantly related to the mammalian cytokine receptor family - Chen, Hua-Wei (Cold Spring Harbor Laboratory Press, 2002)
The JAK/STAT signal transduction pathway controls numerous events in Drosophila melanogaster development. Receptors for the pathway have yet to be identified. Here we have identified a Drosophila gene that shows embryonic mutant phenotypes identical to those in the hopscotch (hop)/JAK kinase and marelle (mrl)/Stat92e mutations. We named this gene master of marelle (mom). Genetic analyses place mom's function between upd (the ligand) and hop. We further show that cultured cells transfected with the mom gene bind UPD and activate the HOP/STAT92E signal transduction pathway. mom encodes a protein distantly related to the mammalian cytokine receptor family. These data show that mom functions as a receptor of the Drosophila JAK/STAT signal transduction pathway.